2022
DOI: 10.1021/acs.bioconjchem.2c00034
|View full text |Cite
|
Sign up to set email alerts
|

Dimerization of the Peptide CXCR4-Antagonist on Macromolecular and Supramolecular Protraction Arms Affords Increased Potency and Enhanced Plasma Stability

Abstract: Peptides are prime drug candidates due to their high specificity of action but are disadvantaged by low proteolytic stability. Here, we focus on the development of stabilized analogues of EPI-X4, an endogenous peptide antagonist of CXCR4. We synthesized macromolecular peptide conjugates and performed side-by-side comparison with their albumin-binding counterparts and considered monovalent conjugates, divalent telechelic conjugates, and Y-shaped peptide dimers. All constructs were tested for competition with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 71 publications
4
28
0
Order By: Relevance
“…Infection rates were determined three days later and showed a concentrationdependent inhibition of viral infection by most compounds (Figure 4a,b, Figure S1, Table 1). The 16-mer original EPI-X4 suppressed infection with an IC 50 value in the higher μM range, whereas the optimized peptides EPI-X4 WSC02 and JM#21 were active with IC 50 values of 562 nM and 126 nM, respectively, in accordance with previous data [1], [6], [13], [18]. Antiviral activities for the N-terminally modified EPI-X4 JM#21 variants correlated with values determined for the competition of CXCR4-antibody binding (r = 0.858, p = < 0.005, Pearson correlation).…”
Section: Inhibition Of Cxcr4-tropic Hiv-1supporting
confidence: 91%
See 1 more Smart Citation
“…Infection rates were determined three days later and showed a concentrationdependent inhibition of viral infection by most compounds (Figure 4a,b, Figure S1, Table 1). The 16-mer original EPI-X4 suppressed infection with an IC 50 value in the higher μM range, whereas the optimized peptides EPI-X4 WSC02 and JM#21 were active with IC 50 values of 562 nM and 126 nM, respectively, in accordance with previous data [1], [6], [13], [18]. Antiviral activities for the N-terminally modified EPI-X4 JM#21 variants correlated with values determined for the competition of CXCR4-antibody binding (r = 0.858, p = < 0.005, Pearson correlation).…”
Section: Inhibition Of Cxcr4-tropic Hiv-1supporting
confidence: 91%
“…Viruses utilizing CD4 and CXCR4 are termed X4-tropic, and viral entry can be inhibited by the ligands CXCL12 [16], EPI-X4, or AMD3100 [1], [17]. As we have previously shown that an increased CXCR4 antagonizing activity of EPI-X4 derivatives largely correlates with antiviral activity against X4-HIV-1 [6], [18], we here determined the antiviral activity of the N-terminally modified variants. For this, TZM-bl reporter cells expressing CD4 and CXCR4 were incubated with the respective compounds and infected with X4-HIV-1.…”
Section: Inhibition Of Cxcr4-tropic Hiv-1mentioning
confidence: 99%
“…To increase the CXCR4 binding affinity to clarify the mechanism of CXCR4 inhibition, we performed SAR studies that resulted in the development of truncated and sequence optimized derivatives EPI-X4 WSC02 (IVRWSKKVPCVS) and EPI-X4 JM#21 (ILRWS-RKLPCVS) [7,8], which have an about 100-fold and 300-fold higher antagonistic activity compared to EPI-X4, respectively [7,8]. In addition, both peptides contain a cysteine (Cys) residue near the C-terminus, which was introduced for the conjugation of functional groups and polymers [12]. Using the CXCR4 antibody-competition assay, we previously found and here confirmed that both derivatives are inactivated in human plasma, with half-lives of only 9 minutes for EPI-X4 WSC02 and 6 minutes for EPI-X4 JM#21, respectively [8,15].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, functional groups (e.g. fluorophores, polymers, or chelators) can be coupled to the peptides C-terminus without interrupting receptor interaction [12]. To do so, a cysteine was introduced in the sequence of both peptides at position 10 [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…This trend was also observed when other linkers such as PEG, PVA and PVP were used. 119 In addition to receptors on the cell surface, intracellular signalling proteins have also been targeted via ACPs. For example, adaptor proteins such as Grb7 mediate important signalling cascades and serves as a therapeutic target.…”
Section: Acps Which Alter Tumor Growth and Block Metastasismentioning
confidence: 99%